Advance Reservations And Scheduling For Bulk Transfers In Research Networks (International Journal of Engineering and Computer Science, 2017)
Data-intensive e-science collaborations often require the transfer of large files with predictable performance. To meet this need, we design novel admission control (AC) and scheduling algorithms for bulk data transfer in research networks for e-science. Due to their small sizes, the research networks can afford a centralized resource management platform. In our design, each bulk transfer job request, which can be made in advance to the central network controller, specifies a start time and an end time. If admitted, the network guarantees to complete the transfer before the end time. To improve the network resource utilization or lower the job rejection ratio, the network controller solves optimization problems in making AC and scheduling decisions. Our design combines the following elements into a cohesive optimization-based framework: advance reservations, multipath routing, and bandwidth reassignment via periodic